Effect of interventions in pregnant women with mildly impaired glucose tolerance. Issue 6 (4th April 2021) - Shindo, Ryosuke; Aoki, Shigeru; Kasai, Junko; Nakanishi, Sayuri; Saigusa, Yusuke; Miyagi, Etsuko
Abstract: Aim: In 2010, the Japan Society of Obstetrics and Gynecology (JSOG) changed the diagnostic criteria for gestational diabetes mellitus (GDM) to follow the International Association of Diabetes and Pregnancy Study Group (IADPSG) criteria. As a result, many pregnant women with mildly impaired glucose tolerance (IGT) were newly diagnosed with GDM. This study aimed to verify the effects of interventions in pregnant women with mild IGT who were newly diagnosed with GDM based on the present JSOG criteria. Methods: We defined mild IGT as a degree of IGT that would be diagnosed as GDM according to the present but not the previous JSOG criteria. We compared pregnancy and delivery outcomes in women with mild IGT who delivered a singleton at 22 weeks of gestation or later, between 2000 and 2009 (untreated group, n  = 503) versus between 2011 and 2017 (treated group, n  = 781). Results: The incidence of GDM‐related composite complications such as macrosomia, shoulder dystocia, neonatal hypoglycemia, neonatal hyperbilirubinemia, and neonatal respiratory distress syndrome was comparable in the untreated and treated groups (10.1% vs. 11.9%, p  = 0.11). The pregnancy outcomes were also comparable, except for infant birth weights, which were lower in the treated group than in the untreated group (3014 g vs. 3094 g; p  = 0.02). Conclusions: Pregnancy outcomes were not affected by the interventions in pregnant women with mild IGT.